2018
DOI: 10.3390/nu10111754
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Five Structurally Diverse Flavonoid Subgroups against Chronic Alcohol-Induced Hepatic Damage in a Mouse Model

Abstract: Alcoholic liver disease (ALD) has become one of the major global health problems, with augmented morbidity and mortality. Evidence indicates that flavonoids can reduce the risk of ALD owing to their biological properties. However, the effect of structurally different flavonoid subclasses on alleviating alcohol-induced liver damage in a same model has never been studied. In this study, mice were supplemented with five kinds of flavonoid subgroups, apigenin (flavone), quercetin (flavonol), naringenin (flavanone)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 38 publications
4
50
0
Order By: Relevance
“…Notably, we found that flavonoids in A. conyzoides significantly decreased the serum levels of AST in mice, indicating that flavonoids in A. conyzoides have protective effects on hepatic function in mice. This is consistent with results in many previous researches that flavonoids could exert considerable protections against the hepatic damages induced by various causes [24,25].…”
Section: Agingsupporting
confidence: 93%
“…Notably, we found that flavonoids in A. conyzoides significantly decreased the serum levels of AST in mice, indicating that flavonoids in A. conyzoides have protective effects on hepatic function in mice. This is consistent with results in many previous researches that flavonoids could exert considerable protections against the hepatic damages induced by various causes [24,25].…”
Section: Agingsupporting
confidence: 93%
“…Their work also helps with the structure identification of the melanin derived from Lachnum YM226. Zhao et al applied a 5 week-long varied flavonoid treatment of EtOH-fed ICR mice, which concluded in noticeable alleviation of liver inflammation and NF-κB activity, as well as a significant reduction in COX-2 [ 182 ]. However, some of the applied flavonoids were more or less efficient in restoring particular functions, e.g., apigenin increased SOD and GSH levels, whilst naringenin reduced iNOS activity most efficiently.…”
Section: Nf-κb Activity Research In Alcohol-related Liver Injury Amentioning
confidence: 99%
“…However, some of the applied flavonoids were more or less efficient in restoring particular functions, e.g., apigenin increased SOD and GSH levels, whilst naringenin reduced iNOS activity most efficiently. Due to the complexity of this paper and different results, we recommend the interested readership to refer directly to [ 182 ]. Radic et al showed, in a study on a 6-week EtOH-fed chronic rat model, that whey can also reverse the EtOH-induced NF-κB activity levels in the liver.…”
Section: Nf-κb Activity Research In Alcohol-related Liver Injury Amentioning
confidence: 99%
“…The EtOH (current study) caused an increased expression of both apoptotic (caspase-3) and antiapoptotic (survivin) markers, and those changes were alleviated by GLE, which correlated well with its hepatoprotective effects demonstrated in the current study. Importantly, grape-seed extract was previously found to exert neuro-, cardio-, and renoprotective effects via apoptosis suppression [55,56], with no previous reports on the antiapoptotic effects of GLE in the liver.…”
Section: (A)mentioning
confidence: 99%